Coaching Evaluation for Women's Volleyball Sports Year 2018 Semarang City (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2019)
The objectives of this research are: (1) Elaborating the antecedent of women's volleyball sports coaching programs in Semarang City; (2) Elaborating transaction programs for training, consumption, welfare, transportation, coordination, organization; and (3) Elaborating the outcome of women's volleyball sports coaching achievements in Semarang City. This research is a qualitative research. The results of this research are: (1) Antecedent The implementation of volleyball coaching in the Mitra Kencana, Talenta, and Taruna Merah Putih clubs is going well, the government support through KONI Semarang City and Regional Government Semarang City is going well, and the process of selecting athletes and receiving coaches that seem simple are carried out by the management; (2) Transaction (process) coaching volleyball at Mitra Kencana, Talenta, and Taruna Merah Putih clubs in Semarang City which consists of aspects of the implementation of training programs, consumption, welfare, and transportation has been well implemented based on real data and facts in the field, only aspects of program implementation training are moderate achieving; (3) The outcome of coaching in Mitra Kencana, Talenta, and Taruna Merah Putih clubs has increased achievements in participating in the provincial level championships in National and Central Java. The conclusions from this research are that overall the antecedent, transaction, and outcome of the training of volleyball sports in Mitra Kencana, Talenta, and Taruna Merah Putih clubs on Semarang city has been going well with the revision of the components in the coaching program so that it can advance the coaching system and improve achievement.